Optical Interferometry A Multidisciplinary Technique in Science and Engineering - Bhowmick, Mithun (IntechOpen, 2022)
Optical interferometry has always been at the heart of interdisciplinary applications. For decades the subject has expanded from fundamental physics and astronomy projects to engineering and telecommunications studies. With the most recent technologies available, along with an extremely well-connected community ready to employ them, the application domain has advanced into other, less explored areas of research. The aim of this book is to review recent developments in OI techniques and aid readers in their exploration of different aspects of the subject. The focus of the novel reports presented in this volume ranges from traditional topics to newer applications, such as those related to biology and clinical procedures. Although this collection of articles is by no means exhaustive, efforts have been made to provide examples and discussions from as many different areas of this wide-ranging subject as possible.